CONSTITUTIONAL AND REGULATORY ANALYSIS IN LAW NO. 20 OF 2003 ON THE NATIONAL EDUCATION SYSTEM: A LITERATURE REVIEW - Hernita; Gunawan Widjaja (International Journal of Teaching and Learning, 2025)
This study aims to analyse the constitutional and regulatory basis contained in Law No. 20 of 2003 on the National Education System through a literature review approach. The analysis of the constitutional basis focuses on the relationship between the Law and the principles and provisions of the 1945 Constitution, particularly regarding the right to education, the obligations of the state, and the basic values of national education. Meanwhile, the regulatory analysis examines the implementation mechanisms, government authority, national education standards, and community participation in the education system regulated by this Law. The results of the study show that Law No. 20 of 2003 is strongly aligned with the constitutional basis and provides a comprehensive regulatory framework. However, implementation challenges require continuous improvement so that national education can be effective, inclusive, and equitable. This study provides recommendations to strengthen constitutional and regulatory aspects in supporting the development of a national education system that is adaptive to social changes and future needs.